2007
DOI: 10.1128/mmbr.00035-06
|View full text |Cite
|
Sign up to set email alerts
|

Functional Taxonomy of Bacterial Hyperstructures

Abstract: SUMMARY The levels of organization that exist in bacteria extend from macromolecules to populations. Evidence that there is also a level of organization intermediate between the macromolecule and the bacterial cell is accumulating. This is the level of hyperstructures. Here, we review a variety of spatially extended structures, complexes, and assemblies that might be termed hyperstructures. These include ribosomal or “nucleolar” hyperstructures; transertion hyperstructures; putative phosphotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 291 publications
(316 reference statements)
0
53
0
Order By: Relevance
“…The divisome is a dynamic hyperstructure (Norris et al, 2007). Its assembly is mediated by multiple protein interactions.…”
Section: Discussion Ftsw and Pbp3 Form A Subcomplexmentioning
confidence: 99%
“…The divisome is a dynamic hyperstructure (Norris et al, 2007). Its assembly is mediated by multiple protein interactions.…”
Section: Discussion Ftsw and Pbp3 Form A Subcomplexmentioning
confidence: 99%
“…It has also become clear that the higherorder chromatin structure and the nuclear architecture are important for efficient repair and genome maintenance (Misteli & Soutoglou, 2009). The concept of DNA repair hyperstructures may also be true for prokaryotes (Norris et al, 2007). Visualization of DNA DSB repair in live Bacillus subtilis cells revealed that RecN protein is recruited to the break followed by RecO and RecF proteins (Kidane et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Because cells in vivo are crowded with biomacromolecules, typically about a 20 to 30% volume fraction (77,78,265), the bag model has been challenged by concepts of higher-order structural elements derived from biochemical and physiological functions. For example, "metabolons" and "quinary" protein structures have been suggested to channel metabolites directly from one catalytic site to another (135,179,207,208,242), and a number of "hyperstructures" (154) have been enumerated to exemplify the concept of modular cytology (91). Such structural and functional elements are intuitively appealing because they could represent higher-order building blocks that make up a cell.…”
Section: Introductionmentioning
confidence: 99%
“…How are these complex cytological structures organized and related to the multiplexes at this coarse microscopic level? Though at this point the multiplexes are only hypothesized physicochemical entities, they may represent biochemical or physiological constructs or hyperstructures (154) at appropriate times during the cell cycle, such as the divisome or stressosome, derived from physiological behavior; other "-omes" could be found by analyses of genomewide interactomes of sys- FIG. 5.…”
mentioning
confidence: 99%